Evaluation of educational interventions on breastfeeding in nursing mothers hospitalized in a teaching maternity hospital in Teresina - PI (Research, Society and Development, 2021)
Breast milk is the most complete food, with an adequate composition of nutrients necessary for the development and growth of the infant up to the sixth month of life, being offered exclusively, in which it must be gradually supplemented until at least two years of age, in this way, contributing to the health of newborns and mothers. This study aimed to evaluate educational health interventions on breastfeeding and develop educational activities on this topic in nursing mothers hospitalized in a teaching maternity hospital in Teresina. The study method was a quantitative descriptive approach, with 100 postpartum women admitted to the maternity hospital. Data were collected through a questionnaire covering level of education, current pregnancy, information about breastfeeding, information about childbirth and postpartum, and knowledge about breastfeeding. Data were compiled from the answers on the forms and later the data were organized and described using tables and graphs in Microsolt excel 2013. Score five was the lowest value observed and score 9, the maximum. The mean and median values, respectively, were 7.97 and 8.0. The mothers have satisfactory levels of knowledge. However, it is still necessary that care services for pregnant women need to follow a protocol that clearly explains the information that must be passed on to them during prenatal care and must be continued in the immediate postpartum period in the maternity hospital.